Dry Eye Syndrome among Game Addicts - Glenn A. S. T. Sormin; Wenny P. Supit; Laya M. Rares (Universitas Sam Ratulangi, 2022)
Abstract: Game is one of the entertainments most often played today. Age differences are not a problem for those who enjoy games. However, the use of computers and cellphones by game addicts can have a bad effect on their health, especially the eye health. Playing games causes lack of eye blinking, therefore, it can cause dry eye syndrome. This study aimed to describe the occurrence of dry eye syndrome due to playing games on game addicts. This was a literature review study using three databases namely ClinicalKey, PubMed, and Google Scholar. The keywords used were Dry Eye Syndrome on game addict. The result showed that external factors such as excessive use of games continuously and playing games that required high concentration caused eye strain and lacks of blinking for a long time without adequate rest were the highest factors that caused dry eye syndrome in game addicts which could occur acutely. This syndrome was often occurred in productive ages from children to adults. In conclusion, dry eye syndrome is highly potential to occur among game addicts. Keywords: dry eye syndrome; game addictionÂ Abstrak: Game merupakan salah satu hiburan yang paling sering dimainkan oleh masyarakat saat ini. Perbedaan usia tidak menjadi masalah bagi pencinta game. Penggunaan komputer dan gawai oleh pecandu game dapat berdampak buruk bagi kesehatan terutama kesehatan mata, Bermain game menyebabkan kurangnya kedipan mata sehingga dapat menyebabkan dry eye syndrome. Penelitian ini bertujuan untuk mendeskripsikan terjadinya dry eye syndrome akibat bermain game pada pecandu game. Jenis penelitian ialah suatu literature review. Pencarian data menggunakan tiga database ClinicalKey, PubMed, dan Google Scholar dengan kata kunci Dry eye syndrome on game addict. Hasil penelitian menunjukkan bahwa faktor eksternal seperti penggunaan game yang berlebihan terus menerus dan jenis game konsentrasi tinggi menyebabkan ketegangan mata, dan kurang berkedip dalam waktu lama tanpa istirahat yang merupakan faktor tertinggi penyebab dry eye syndrome pada pecandu game yang dapat terjadi secara akut, lebih sering terjadi pada usia produktif mulai dari anak hingga dewasa. Simpulan penelitian ini ialah dry eye syndrome berpotensi tinggi terjadi pada pecandu game.Kata kunci: sindroma dry eye; game addiction